Pengaruh Kinerja Keuangan Terhadap Nilai Saham PT Astra Agro Lestari Tbk di Bursa Efek Indonesia Periode 2020–2024 - Andi Asti Astagina; Abdul Mutalib; Sahabuddin N (Jurnal Ekonomi Islam, 2026)
This study aims to examine the effect of financial performance, specifically measured through the Current Ratio (CR), Debt to Assets Ratio (DAR), and Earnings Per Share (EPS), on the stock price of PT Astra Agro Lestari Tbk listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. The research uses a quantitative associative approach and secondary data from the company's annual financial reports, with analysis conducted through multiple linear regression using SPSS version 26. The results show that, partially, the Current Ratio (CR) and Debt to Assets Ratio (DAR) have a positive and significant effect on the stock price, whereas Earnings Per Share (EPS) has a significant effect with the negative direction. Simultaneously, CR, DAR, and EPS collectively exert a significant influence on the stock price, with an adjusted coefficient of determination (R2) of 86.1%, confirming that the regression model possesses a strong capability in explaining the variations in the stock price.